2016
DOI: 10.1038/srep35489
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-2 alpha promotes the proliferation of human placenta-derived mesenchymal stem cells through the MAPK/ERK signaling pathway

Abstract: Human placenta-derived mesenchymal stem cells (hPMSCs) reside in a physiologically low-oxygen microenvironment. Hypoxia influences a variety of stem cell cellular activities, frequently involving hypoxia-inducible factor-2 alpha (HIF-2α). This research showed that hPMSCs cultured in hypoxic conditions (5% O2) exhibited a more naïve morphology and had a higher proliferative capability and higher HIF-2α expression than hPMSCs cultured in normoxic conditions (21% O2). Similar to the hypoxic cultures, hPMSCs over-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 31 publications
3
47
0
2
Order By: Relevance
“…MAPK family transduction proteins include ERK, p38 kinase, and JNK, among others [ 89 ]. Although p38 and ERK have been shown to play important roles in mediating stem cell proliferation and differentiation [ 90 92 ], their specific involvement in the differentiation into hepatocytes remains unclear. The Ras-Raf-MEK-ERK pathway phosphorylates a spectrum of substrates and plays an integral role in cell cycle progression and survival [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…MAPK family transduction proteins include ERK, p38 kinase, and JNK, among others [ 89 ]. Although p38 and ERK have been shown to play important roles in mediating stem cell proliferation and differentiation [ 90 92 ], their specific involvement in the differentiation into hepatocytes remains unclear. The Ras-Raf-MEK-ERK pathway phosphorylates a spectrum of substrates and plays an integral role in cell cycle progression and survival [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia increased the proliferation of MSCs when compared to standard oxygen levels used for cell culture (Zhu et al, 2016). Moreover, cells under hypoxic conditions maintain their undifferentiated status and multipotency (Basciano et al, 2011).…”
Section: Contrasting Results In Clinical Trials: Not All Mscs Are Equalmentioning
confidence: 97%
“…Hypoxia inducible factor (HIF) pathway may be the trigger to the enhanced mechanism of MSCs in hypoxia, among which HIF-1α and HIF-2α are key molecules that have protective effects on MSCs. Chang et al demonstrated that HIF-2α maintained MSCs cell viability and promoted cell proliferation related to the regulation of CyclinD1 (CCND1) and c-Myc (MYC) by the MAPK/ERK signaling pathway [61]. Similarly, Bingke et al reported that HIF-1α was associated with the increasing of cell activity and the suppression of MSCs apoptosis under hypoxia conditions [62].…”
Section: Influence Of Oxygen Concentrationmentioning
confidence: 99%